Implementation of Solving Criminal Cases (Splitsing) in the Proof Process in Criminal Trials - Kamila, Firyal; Yanuar, Iyang; Nurdiansyah, Rizki (JURNAL RUANG HUKUM, 2022)
The role of a witness who is also an actor in the same case is referred to as a witness who is also a suspect "crown witness". The role of a witness is really needed to uncover a crime that was committed by more than one person together. To uncover evidence of who was involved, what were the roles of the perpetrators and how the crime could be committed. The purpose of this study is to find out how splitsing is implemented in criminal cases. The method used is philosophy juridical with a statutory and case approach, this study uses secondary data supported by primary legal materials such as laws, secondary legal materials in the form of journals and books. The results of this study indicate that the testimony of other defendants was carried out by the public prosecutor who has the authority to split the case files (spiltsing) so that the public prosecutor can reveal the testimony of witnesses and defendants that are the same or different and make it easier to find out the main perpetrators of the crime. The basis for separating the case files is in Article 142 of the Criminal Procedure Code.